1995
DOI: 10.1577/1548-8659(1995)124<0935:nuodav>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Notes: Utility of Depth and Velocity Preferences for Predicting Steelhead Parr Distribution at Different Flows

Abstract: We tested an assumption of the instream flow incremental methodology that depth and velocity preferences are independent of streamflows. We had previously developed depth and velocity preferences (P[d\ and P[v]) for juvenile (parr) steelhead Oncorhynchus mykiss at 0.86 m-Vs in Morse Creek, Washington, and found parr distributed in microhabitats with higher combined depth-velocity preference (P[dv\ = P[d] X P[v]) at a similar flow (0.69 nvVs). In the present study, we evaluated the relationship between fish di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 10 publications
0
25
1
Order By: Relevance
“…Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden. Terms & Conditions of access and use can be found at http://www.tandfonline.com/ page/terms-and-conditions Beecher et al (1995) should be commended for trying to test one of the various assumptions of the physical habitat simulation model (PHAB-SIM). They noted Shirvell's (1990) report that juvenile steelhead Oncorhynchus mykiss used areas of stream with different water velocities at different flows, which suggested that the microhabitat preferences of juvenile steelhead can be a function of flow.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 4 more Smart Citations
“…Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden. Terms & Conditions of access and use can be found at http://www.tandfonline.com/ page/terms-and-conditions Beecher et al (1995) should be commended for trying to test one of the various assumptions of the physical habitat simulation model (PHAB-SIM). They noted Shirvell's (1990) report that juvenile steelhead Oncorhynchus mykiss used areas of stream with different water velocities at different flows, which suggested that the microhabitat preferences of juvenile steelhead can be a function of flow.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…In an earlier study, Beecher et al (1993) developed preference criteria for depth and velocity from observations of 104 juvenile steelhead at a relatively low flow (Figure 1). In a later study, Beecher et al (1995) measured depth and velocity at regular intervals along evenly spaced transects in an adjacent reach of the same stream at a relatively high flow. This gave them data at 242 points on a grid, which they took to represent an equal number of PHABSIM cells.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 3 more Smart Citations